PENGARUH CITA RASA DAN HARGA TERHADAP MINAT BELI MAKANAN TRADISIONAL BHOI ACEH DI KECAMATAN PEUKAN BARO KABUPATEN PIDIE (Studi Kasus Pada Dhapu Bhoi) - Eka Agustina; Darmi Darmi; Tuti Rahmah (Universitas Jabal Ghafur, 2023)
This study aims to determine and analyze the effect of taste on buying interest in traditional Bhoi Aceh food in Peukan Baro District, Pidie Regency. Where the independent variables namely Taste, Price and Purchase Intention (Y) as the dependent variable. The population in this study is a comparison of the increase in the interest in buying traditional Bhoi Aceh food at culinary Dhapu Bhoi in 2023 as many as 250 people. Determination of sample size in this study was carried out using the Slovin formula as many as 71 people. The data collected in this study consisted of primary data and secondary data, both qualitative and quantitative data and through questionnaires filled out by respondents. Then the data obtained were analyzed using multiple regression analysis. This analysis includes Normality Test, Multicollinearity Test, Heteroscedasticity Test Classical Assumption Test, Hypothesis Test through F test and t test, and analysis of the Coefficient of Determination (R²). Based on the research results, the regression equation is obtained: Y = 5.750 + 0.381 X1 + 0.285 X2. The results of the analysis based on the t test show that the Taste (X1) and Price (X2) variables significantly influence the intention to buy traditional Bhoi Aceh food in Peukan Baro District, Pidie Regency (Case Study on Dhapu Bhoi Culinary). The results of the analysis show that the Taste variable (X1) has the most dominant influence, namely 0.381 or 38.1% on the intention to buy traditional Bhoi Aceh food in Peukan Baro District, Pidie Regency (Case Study on Dhapu Bhoi Culinary). The relationship between the dependent and independent variables, namely each variable Taste (X1) and Price (X2) on the intention to buy traditional Bhoi Aceh food in Peukan Baro District, Pidie Regency (Case Study on Dhapu Bhoi Culinary) with a correlation coefficient of 0.686. This means that the relationship is very strong. The coefficient of determination for the Taste (X1) and Price (X2) variables is 0.4712 = 0.222, this means that there is an influence on the interest in buying traditional ABhoi Aceh food in Peukan Baro District, Pidie Regency (Case Study on Dhapu Bhoi culinary) of 22.2% , while the remaining 77.8% is influenced by other variables not examined in this study.